INGLIZCHA-O‘ZBEKCHA LUG‘AT HAQIDA - Ruzimov, Sh. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of principles of compelling the English-Uzbek dictionary by Sh.Butaev and A.Irisqulov by the method of componential analysis and comparative-typological method. On the basis of examples there were distinguished its advantages and disadvantages and presented some practical recommendations for improving principles of compiling dictionaries. The author’s recommendations are of a practical value for improving of the quality of bilingual dictionaries.
Keywords: lexicography; synonym; stress; principles; critically; recommendations; to work out; whole system; scientific; investigate